Limites da autoexecutoriedade do poder de polícia - Gonçalves, Leonardo de Mello (2010)
The goal of this work is to do an analysis of the administrative act self execution, verifying the hypothesis and the limits for its usage, in the context of redefining Administrative Law according to Democratic State of Law and fundamental rights. It is easy to notice that a referring point appears more intensively in police power actions which are the disciplinary administrative functions of citizens liberty and properties. Those functions rule their lives in their communities by imposing limits (what not to do) and enforcing duties (what to do) in a preventing or repressive way. It means that Administration itself can, on its own, execute police actions, without having to recur to juridical procedures. The application of self execution by Administration does not mean a violation of Judiciary inseparability principle that is showed in the 5th article 35th item of the 1988 Federal Constitution because the subject can appeal to impede it or even cancel the action. Moreover in case of overpowering or non accordance with the conditions to perform such action it can be suspended or canceled. The fact is that Administration executes administrative function and so it must satisfy public interests (of the community) and not interests or preferences of its own organization or state agents. Therefore self execution or any other related items are only instruments to be used to achieve public interests by observing the right opportunity and the right measure to do it. Concluding, in a Democratic State of Law, similar to that followed in Brazil, the Federal Constitution presents a normative system of duties attribution which leads the state work. And there are also limits for that work based on the list of rights and fundamental guarantees that represents citizens protection. Finding limits to state work and not allow that it can affect citizens rights and guarantees is a necessary action to show the state fair actuation and to impede the violation of fundamental rights that were hardly achieved